Microcavity engineering for scalable, efficient polaritonic applications - Qureshi, Hassan Ali (fi=Turun yliopisto|en=University of Turku|, 2026)
Optical microcavities provide a powerful platform for tailoring light–matter interaction through optical confnement, spectral selectivity, and electromagnetic feld enhancement. When combined with organic semiconductors, microcavities enable spectral narrowing, angle-dependent dispersion, and, in the strong coupling regime, the formation of exciton-polaritons, hybrid light-matter quasiparticles with low effective mass and high spatial delocalization. The performance and scalability of polaritonic systems therefore depend critically on microcavity design and fabrication. This dissertation investigates microcavity engineering for scalable polaritonic ap plications using solution-processed and vacuum-fabricated architectures. The fundamental principles of optical confnement in planar microcavities are established, providing a framework for understanding confned light-matter interaction. Strong coupling and exciton-polariton formation are demonstrated in hybrid and fully solution-processed dielectric distributed Bragg refector microcavities fabricated by dip-coating and spin-coating. An automated deposition approach enables reproducible multilayer control, yielding microcavities with quality factors exceeding 200 using a limited number of DBR pairs. Angle-resolved refectivity and photo luminescence measurements reveal clear anticrossing behavior and large Rabi splittings. Under non-resonant optical excitation above a critical pump fuence of ap proximately 20 cm−2 , these microcavities exhibit nonlinear emission and room temperature polariton lasing. The thesis also examines polaritonic microcavity engineering in vacuum-fabricated organic light-emitting diode architectures. Time-resolved electroluminescence mea surements show that delayed emission is dominated by trap-assisted processes, in dicating negligible infuence of polaritons on intramolecular excited-state dynamics. Microcavity and surface plasmon polariton mode engineering further enable spectral and color control, yielding single-emitter, top-emitting white OLEDs with tunable color temperature. Overall, this work demonstrates microcavity engineering as a viable strategy for scalable polariton physics and practical optoelectronic devices.